2012
DOI: 10.1080/01639625.2011.584054
|View full text |Cite
|
Sign up to set email alerts
|

Self-Cutting and Suicidal Ideation among Adolescents: Gender Differences in the Causes and Correlates of Self-Injury

Abstract: In recent years, non-suicidal self-injury (NSSI) among adolescents has been identified as alarmingly common place. Some studies have suggested that more than one in eight adolescents have engaged in self-cutting or other self-injuring behaviors. Even more of a concern is that self-injury often foreshadows suicide or suicide attempts. With self-cutting common in middle and high schools, understanding the antecedents and correlates of such behavior may help counselors and others public health officials identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 58 publications
6
60
1
1
Order By: Relevance
“…Participating women had significantly higher levels than those who identified as men, consistent with the established trend that women experience psychological distress and nonsuicidal self-injury at higher rates (Bakken & Gunter, 2012;Norman, 2004;Russell & Joyner, 2001). Younger participants also had significantly higher levels of nonsuicidal self-injury, consistent with the previous research (Walls, Laser, et al, 2010).…”
Section: Predictors For Gay and Lesbian Peoplesupporting
confidence: 61%
See 1 more Smart Citation
“…Participating women had significantly higher levels than those who identified as men, consistent with the established trend that women experience psychological distress and nonsuicidal self-injury at higher rates (Bakken & Gunter, 2012;Norman, 2004;Russell & Joyner, 2001). Younger participants also had significantly higher levels of nonsuicidal self-injury, consistent with the previous research (Walls, Laser, et al, 2010).…”
Section: Predictors For Gay and Lesbian Peoplesupporting
confidence: 61%
“…People who are racial minorities or members of a lower socioeconomic status exhibit more depressive symptoms, which are linked to nonsuicidal selfinjury (Bakken & Gunter, 2012;Walsh, Levine, & Levav, 2012). Because higher education may be less accessible to racial/ethnic minorities and members of lower socioeconomic statuses, the education measure might have assessed these variables by proxy.…”
Section: Predictors For Gay and Lesbian Peoplementioning
confidence: 99%
“…This complexity might explain why some studies report that females are more likely to engage in self-harm (e.g., Sornberger, Heath, Toste, & McLouth, 2012), whereas other studies report no gender differences (e.g., Guan, Fox, & Prinstein, 2012). The effect of gender on self-harm might actually stem from abuse history and abuse-related intrapersonal factors, not gender itself (N. W. Bakken & Gunter, 2012), as the likelihood of experiencing certain kinds of abuse varies by gender (Goldberg & Freyd, 2006;Gratz et al, 2002). Therefore, understanding the complex etiology of self-harm, including the effect of gender, requires inclusion of abuse history (Zoroglu et al, 2003), as to decrease the likelihood of misguided or erroneous findings (Becker-Blease, Freyd, Russo, & Rich-Edwards, 2012).…”
Section: Gender Abuse History Nonsuicidal Self-injury and Attemptementioning
confidence: 90%
“…Hay and Meldrum (2010) also showed that bullying victimization was significantly and positively associated with NSSI. More recently, Bakken and Gunter (2012) and Alfonso and Kaur (2012) also found that individuals who reported high levels of victimization were more likely to engage in self-injury with or without suicidal intent than those who reported low levels of victimization. Additionally, bullies showed an increased risk to engage in suicidal as well as NSSI behaviors, certainly when they had a history of being bullied, the so called bully-victims (Barker et al 2008).…”
Section: Introductionmentioning
confidence: 97%